DIGITAL STORYTELLING IN TEACHING FOREIGN LANGUAGES (American Journal of Interdisciplinary Research and Development, 2024)
Communicative language teaching has emerged in second and foreign language pedagogy due to the inadequacy of previous language teaching methods to enhance English as a foreign language (EFL) learners’ communicative competence. However, old language teaching methods, mainly, grammar-translation and audio-lingual, are still prevalent in EFL contexts. One of the reasons behind EFL teachers’ hesitance to shift entirely to communicative language teaching (CLT) is the absence of clear guidance, including examples for classroom activities appropriate for this approach. Thus, the aim of this study is, first, to bridge this gap by suggesting digital storytelling as a classroom activity that is well aligned with the principles of the communicative language approach. Second, to assess the effectiveness of digital storytelling activity on improving some linguistic aspects of students’ communicative competence.